KESIAPAN ORANG TUA DALAM PENGELOLAAN PENDIDIKAN ANAK USIA DINI - Jamilah Jamilah (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
The study aims to analyze the readiness of parents in the implementation of Tarbiyatus Shibyan's early childhood education program. This type of research uses qualitative research with a case study approach. The location of this study was carried out in Tarbiyatus Shibyan Jadung Dungkek Sumenep's Early Childhood Education. The subject of the study was an elderly person who sent his child to school in early childhood education Tarbiyatus Shibyan. The collection of data using interviews, observation, documentation and Focus Group Discussion. Data analysis consisted of data collection, data presentation and conclusion drawing. This research results in finding that the readiness of parents in organizing early childhood education is active.